The power of the dog a novel - Savage, Thomas 1915-2003 (Back Bay Books - Little Brown and Company, 2021)
"Set in the wide-open spaces of the American West, The power of the dog is a stunning story of domestic tyranny, brutal masculinity, and thrilling defiance from one of the most powerful and distinctive voices in American literature. The novel tells the story of two brothers--one magnetic but cruel, the other gentle and quiet--and of the woman and boy, a mother and son, whose arrival on the brothers' ranch shatters an already tenuous peace. From the novel's startling first paragraph to its very last word, Thomas Savage's voice--and the intense passion of his characters--holds readers in thrall."--Back cover
Hier auch später erschienene, unveränderte Nachdrucke
Auf dem Cover: "Netflix - a Netflix film"
Keywords: Brothers / Fiction; Mothers and sons / Fiction; Ranch life / Fiction; Families / Fiction; Montana / Fiction; Frères / Romans, nouvelles, etc; Mères et fils / Romans, nouvelles, etc; Vie au ranch / Romans, nouvelles, etc; Familles / Romans, nouvelles, etc; Montana / Romans, nouvelles, etc; Brothers; Families; Mothers and sons; Ranch life; Montana; Domestic fiction; Fiction; Historical fiction; Fiktionale Darstellung